Evaluation of drug release from fatty based suppository: the difference between intrinsic and non-intrinsic dissolution methods - ., Marchaban (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Study on the difference of evaluation methods, namely intrinsic and non-intrinsic dissolution methods, on the drug release from fatty-based suppository has been performed. The study was done by producing the suppositories consisting of 50, 100, 150, 200 and 250 mg of sodium salicylate respectively. The drug release from the suppositories was then evaluated using intrinsic dissolution apparatus that limited the contact area of the suppository with the medium, and non-intrinsic that not limited its contact area. The aim of the study was to know the difference of the drug release profiles if they are evaluated using intrinsic and non-intrinsic dissolution methods.The results showed that the drug release using non-intrinsic dissolution method was always higher than that of the intrinsic method at any drug concentration, the drug concentration has not showed proportional relationship with their release although the drug release tend to be higher as the concentration was higher.Key words: suppository, dissolution